The Rise of Marine Mammals : 50 Million Years of Evolution - Berta, Annalisa (Book collections on Project MUSE., 2017)
Marine mammals have long captured the attention of humans. Ancient peoples etched seals and dolphins on the walls of Paleolithic caves; today, engineers develop microprocessors to track these denizens of the deep. This groundbreaking book from highly respected marine mammal paleontologist Annalisa Berta delves into the story of the extraordinary adaptations that gave the world these amazing animals. The Rise of Marine Mammals reveals remarkable fossil record discoveries that shed light on the origins, relationships, and diversification of marine mammals. Focusing on evolution and paleobiology, Berta provides an overview of marine mammal species diversity, enhanced with gorgeous life restorations by Carl Buell, Robert Boessenecker, William Stout, and Ray Troll and extensive line drawings by graphics editor James L. Sumich. The book also considers ongoing conservation challenges, demonstrating how the fossil record of adaptation in response to past environmental shifts may illuminate the way that marine mammals respond to global climate change. This invaluable evolutionary framework is essential for helping us understand how best to protect and conserve today's polar bears, whales, dolphins, seals, and fellow warm-blooded ocean dwellers. The Rise of Marine Mammals also describes exciting breakthroughs that rely on new techniques of study, including 3-D imaging, and molecular, finite element, and morphometric analyses, which have enhanced scientists' understanding of everything from the anatomy of fetal whales to the genes behind limb loss in cetaceans. Mammalogists, paleontologists, and marine scientists will find Berta's insights absorbing, while developmental and molecular biologists, geneticists, and ecologists exploring integrative research approaches will benefit from her fresh perspective.